PENGARUH LINGKUNGAN KERJA, MODEL PEMBELAJARAN, DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA GURU SERTIFIKASI - VERA AFRIYANI; Samsi Samsi; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This research aims to find there is influence of working area, model of teaching learning, and working discipline towards working produktivity of certification teacher in SMK Negeri Kecamatan Metro Timur at the year of 2012/2013. The population is all certification teacher in SMK Negeri Kecamatan Metro Timur that consisted of 101 teachers which the sample is 81 teachers. Simple linier regression used for testing hypothesis 1, 2, 3, and for testing hypothesis 4 by using multiple linier regression. From the analysis was found that: (1) there was influence of working area towards working productivity of certification teacher about 39,9%. (2) there was influence model of teaching learning towards working productivity of certification teacher about 40,4%. (3) there was influence of working discipline towards working productivity of certification teacher about 38,6%. (4) there was influence of working area, model of teaching learning, and working discipline towards working productivity of certification about 60,3%.Keywords: Working Area, Model of Teaching Learning, Working Discipline, and Productivity of Certification Teacher.